The Interplay of Instructional Styles, Academic Motivation, and Engagement in an English Language Flipped Classroom Context - Kosal Mao; Daro Ruos; Sereyrath Em (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study was to investigate the relationships between English instructional styles, academic motivation, and academic engagement among Cambodian high school students in grade 12. A correlational design, using a cross-sectional technique, was employed by 510 students using a structured questionnaire. The data analysis employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to assess the measurement and structural model simultaneously, including a mediating study within the 5000-sample bootstrapping method. The findings showed that the measurement model has adequate reliability and validity. With the structural model revealed among instructional styles, support for academic autonomy significantly predicts academic motivation and engagement. Importantly, intrinsic motivation plays a key role in mediating between instructional styles and engagement rather than extrinsic motivation. Support for academic autonomy, followed by support for video lectures, exhibited satisfactory effects indirectly on engagement via intrinsic motivations. These findings underpin the paramount significance of fostering intrinsic motivation by generating autonomous-supportive and well-structured video-based learning climates. As such, instructors should prioritize how to promote autonomous decision-making to enhance students’ sense of competence, autonomy, and relatedness, thereby advancing a profound and more meaningful engagement in English language teaching. Further implications for this study were suggested with a more practical design.